Beneficios de la punción seca en el dolor crónico del cuadrado lumbar - Grover Ronaldo, Pino Cantos (2022)
ABSTRACT In the following investigation carried out in a bibliographic review modality, entitled "Benefits of dry needling in chronic lumbar quadratus pain", the benefits of dry needling in low back pain were analyzed, with the aim of determining the most appropriate treatment protocol. effective in treating chronic quadratus lumborum pain. Clinical trials have been obtained in databases such as: SearchGate, PubMed, Worldwide, PEDro, which are in English and Spanish, providing us with information to carry out the research, in order to select the articles that they provide us, they have been valued by the PEDro scale. Low back pain presents an algia of mechanical principle at some stage of our lives causing localized pain and also disability, by making use of this technique we will help improve the functionality of the patient by reducing hyperirritability, with the performance of dry needling , favorable results are obtained in less time. A documentary investigative work was carried out, an inductive method was applied with a descriptive approach by the analysis of previous investigations, which were 150 at the beginning of the investigation and the articles that complied with the assessment of the PEDro scale were 35, when selecting these articles, the effects of the technique were included when applying it, as well as the superficial and deep puncture, the difference and combination between other treatments, when analyzing and classifying it was possible to observe a great efficiency in the results when said technique was applied. It has been taken into account that it offers good results in the short and medium term. Keywords: quadratus lumborum, dry needling, myofascial pain, hyperirritability.